4000(1.05)⁴=$4862.03
6000(1+ .08/2)^35(2)=$93429.71
15450(.86)³=$9827.07
Answer:
68
Step-by-step explanation:
The expression is given as:
4( 3+ 7y) + 6(2 - y)
It is known that y is equal to 2. Therefore, substitute 2 in for y.
4(3+7(2))+6(2-2)
Now, solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, Subtraction
Solve inside of the parentheses first.
4(3+7(2))+6(2-2)
4(3+14)+6(0)
4(17)+6(0)
Multiply
68+0
Add
68
<h3>
Answer: 3 units</h3>
=============================================================
Explanation:
The y coordinates are identical, so we just need to focus on the x coordinates.
Going from 0 to -3 is a distance of 3 units. Drawing out a number line might help.
Or we could apply subtraction and absolute value
|x1-x2| = |0-(-3)| = |0+3| = |3| = 3
which is the same as
|x2-x1| = |-3-0| = |-3| = 3
The absolute value is to ensure the result is never negative. Distance is never negative.
Side note: if the y coordinates weren't the same, then we'd have to use either the pythagorean theorem or the distance formula.
Answer:
76.3
Step-by-step explanation: